Optical properties of silver nanoparticles embedded in dielectric films produced by dc and rf magnetron sputtering - Tafur, G (2019)
One of us, J.A., is very grateful to CONCYTEC for a scholarship financing doctoral studies. A.T. is also very grateful to Universidad Nacional de Ingeniería and MINEDU Perú for special grants as a researcher professor. We are very thankful to H. Huanca and C. Luyo for achieving our X-ray diffractograms.